Intramolecular carbonickelation of alkenes - Lhermet, Rudy; Durandetti, Muriel; Maddaluno, Jacques (Beilstein Journal of Organic Chemistry, 2013)
The efficiency of the intramolecular carbonickelation of substituted allylic ethers and amines has been studied to evaluate the influence of the groups borne by the double bond on this cyclization. The results show that when this reaction takes place, it affords only the 5-exo-trig cyclization products, viz. dihydrobenzofurans or indoles. Depending on the tethered heteroatom (O or N), the outcome of the cyclization differs. While allylic ethers are relatively poor substrates that undergo a side elimination and need an intracyclic double bond to proceed, allylic amines react well and afford indoline and indole derivatives. Finally, the synthesis of the trinuclear ACE core of a morphine-like skeleton was achieved by using NiBr2bipy catalysis.
Keywords: alkenes; carbometallation; carbonickelation; cyclization; Heck-type reaction; nickel catalysis

Metal-Catalyzed Cross-Coupling Reactions - Marek, I.; Chinkov, N.; Banon-Tenne, D. (Carbometallation Reactions, 2004)

(untitled) - Hogan, A.-M. L.; O’Shea, D. F. (Chem. Commun., 2008)

(untitled) - Ziegler, K.; Bähr, K. (Chem. Ber., 1928)

(untitled) - Heck, R. F.; Nolley, J. P. (J. Org. Chem., 1972)

(untitled) - Heck, R. F. (Acc. Chem. Res., 1979)

(untitled) - Beletskaya, I. P.; Cheprakov, A. V. (Chem. Rev., 2000)

(untitled) - Dounay, A. B.; Overman, L. E. (Chem. Rev., 2003)
See for a review on palladium-catalyzed reactions involving the Mizoroki–Heck reaction.

(untitled) - Negishi, E.-i.; Copéret, C.; Ma, S.; Liou, S.-Y.; Liu, F. (Chem. Rev., 1996)

(untitled) - Ma, S.; Negishi, E.-i. (J. Org. Chem., 1994)

(untitled) - Taniguchi, T.; Zaimoku, H.; Ishibashi, H. (J. Org. Chem., 2009)

The Mizoroki-Heck reaction - Oestreich, M. (John Wiley & Sons, Ltd, 2009)

(untitled) - Rollin, Y.; Meyer, G.; Troupel, M.; Fauvarque, J.-F.; Périchon, J. (J. Chem. Soc., Chem. Commun., 1983)

(untitled) - Olivero, S.; Rolland, J.-P.; Duñach, E. (Organometallics, 1998)

(untitled) - Ma, S.; Wang, H.; Gao, K.; Zhao, F. (J. Mol. Catal. A: Chem., 2006)

(untitled) - Gøgsig, T. M.; Kleimark, J.; Lill, S. O. N.; Korsager, S.; Lindhardt, A. T.; Norrby, P.-O.; Skrydstrup, T. (J. Am. Chem. Soc., 2012)

(untitled) - Durandetti, M.; Gosmini, C.; Périchon, J. (Tetrahedron, 2007)

(untitled) - Gosmini, C.; Bassene-Ernst, C.; Durandetti, M. (Tetrahedron, 2009)

(untitled) - Durandetti, M.; Hardou, L.; Lhermet, R.; Rouen, M.; Maddaluno, J. (Chem.–Eur. J., 2011)

(untitled) - Durandetti, M.; Hardou, L.; Clément, M.; Maddaluno, J. (Chem. Commun., 2009)

(untitled) - Jahn, U. (Radicals in Synthesis III, 2012)
Radical intermediates have been proposed in case of alkylnickel.

(untitled) - De França, K. W. R.; Navarro, M.; Léonel, E.; Durandetti, M.; Nédélec, J.-Y. (J. Org. Chem., 2002)

(untitled) - Jutand, A. (Chem. Rev., 2008)

(untitled) - Burns, B.; Grigg, R.; Sridharan, V.; Worakun, T. (Tetrahedron Lett., 1988)

(untitled) - Gao, P.; Cook, S. P. (Org. Lett., 2012)
See for a recent application.

(untitled) - Tsou, T. T.; Kochi, J. (J. Am. Chem. Soc., 1979)

(untitled) - Olivero, S.; Duñach, E. (Synlett, 1994)

(untitled) - Franco, D.; Wenger, K.; Antonczak, S.; Cabrol-Bass, D.; Duñach, E.; Rocamora, M.; Gomez, M.; Muller, G. (Chem.–Eur. J., 2002)

(untitled) - Durandetti, M.; Nédélec, J.-Y.; Périchon, J. (J. Org. Chem., 1996)

(untitled) - Durandetti, M.; Périchon, J. (Synthesis, 2004)

(untitled) - Anka-Lufford, L. L.; Prinsell, M. R.; Weix, D. J. (J. Org. Chem., 2012)

(untitled) - Uchida, K.; Yokoshima, S.; Kan, T.; Fukuyama, T. (Org. Lett., 2006)

(untitled) - Larock, R. C.; Stinn, D. E. (Tetrahedron Lett., 1988)

(untitled) - Parsons, P. J.; Charles, M. D.; Harvey, D. M.; Sumoreeah, L. R.; Shell, A.; Spoors, G.; Gill, A. L.; Smith, S. (Tetrahedron Lett., 2001)

(untitled) - Trost, B. M.; Tang, W.; Toste, F. D. (J. Am. Chem. Soc., 2005)